How confident are pharmacists in providing pharmaceutical care on anticoagulants? A cross-sectional, self-administered questionnaire study in Borneo, Malaysia - Sze Ling Tan (BMC, 2021)
Abstract Background Anticoagulants are the cornerstone therapy for the management of venous thromboembolism (VTE) and atrial fibrillation (AF). Pharmacists should be confident and equipped with the skill and updated knowledge in managing anticoagulation therapy. Objective To explore self-reported confidence level of pharmacists, perceived reasons influencing their confidence and socio-demographic associated with high confidence level in the area of anticoagulation. Methods A cross-sectional, self-administered questionnaire survey was carried out among fully registered pharmacists who work in selected government hospitals and clinics in Borneo, Malaysia, from January 2019 to February 2020. Results Overall, responses from 542 fully registered pharmacists were obtained. Proportion of respondents who claimed confident in providing necessary information to patient receiving warfarin (n = 479, 88.3%) was significantly higher (p < 0.001) compared to low molecular weight heparins (n = 317, 58.5%) and direct oral anticoagulants (n = 211, 38.9%). Respondents’ perceived reasons that may influence their confidence level include experience in dealing with anticoagulants’ cases (n = 469, 86.5%), knowledge on anticoagulants (n = 394, 72.7%) and knowledge on diseases needing anticoagulation therapy (n = 311, 57.4%). Practising as ward pharmacist and “always” dealing with anticoagulants during their practice were the socio-demographic that significantly associated with high confidence level of pharmacist in providing pharmaceutical care on all types of anticoagulants (p < 0.05). Conclusion Pharmacists were found more confident in providing pharmaceutical care on warfarin compared to low molecular weight heparins and direct oral anticoagulants. Continuous educational and training programmes on the use of anticoagulants should be carried out to enhance pharmacists’ confidence in supporting patients’ care.